Supramolecular diaryliodonium salt‐crown ether complexes as cationic photoinitiators. Issue 4 (5th December 2012) - Crivello, James V.; Aldersley, Michael F.
Abstract Diaryliodonium salts spontaneously form crystalline 1:1 supramolecular complexes at room temperature in good to excellent yields with 18‐crown‐6 ether and its cyclohexano‐ and benzo‐substituted analogs. The complexes were characterized using IR, UV, MS, 1H, and 13C‐NMR spectroscopy and by single crystal X‐ray crystallography. The analytical data obtained were consistent with a structure in which the positively charged iodine atom of diaryliodonium cation is positioned above and over the center of the crown ether ring with the positively charged iodine atom coordinated to the crown ether oxygen atoms. The diaryliodonium salt‐crown ether complexes are photosensitive and were used to carry out the photoinitiated cationic polymerizations of a number of mono‐ and difunctional monomers. During irradiation with UV light, the supramolecular complexes undergo photolysis with the generation of a Brønsted acid and with the concomitant release of the crown ether. When used as photoinitiators, the crown ether that is released markedly influences the kinetics of the subsequent cationic polymerization of the monomer. Further studies demonstrated that the photolysis of diaryliodonium salt‐crown ether supramolecular complexes can be photosensitized using typical‐electron transfer photosensitizers. Free radical‐promoted photosensitization using typical unimolecular free radical photoinitiators such as 2, 2‐dimethoxy‐2‐phenylacetophenone also takes place readily. © 2012 Wiley Periodicals, Inc. J Polym Sci Part A: Polym Chem, 2013